Laser Doppler anemometer signal processing for blood flow velocity measurements. (31st March 2015) - Borozdova, M A; Fedosov, I V; Tuchin, V V
Abstract A new method for analysing the signal in a laser Doppler anemometer based on the differential scheme is proposed, which provides the flow velocity measurement in strongly scattering liquids, particularly, blood. A laser Doppler anemometer intended for measuring the absolute blood flow velocity in animal and human near-surface arterioles and venules is developed. The laser Doppler anemometer signal structure is experimentally studied for measuring the flow velocity in optically inhomogeneous media, such as blood and suspensions of scattering particles. The results of measuring the whole and diluted blood flow velocity in channels with a rectangular cross section are presented.